Seeking Power from Two Different Voices: A Gendered Approach to Freedom Activists’ Speeches - Sulistya Ningtyas (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
Gender basically gives distinction to males and females, where our public domain is inseparable from this social construction. This study aimed to identify the language use of the Middle Eastern freedom activists’ speeches based on gender perspective. The data source was from male and female Middle Eastern freedom activists’ speech videos. A number of participants were also involved to measure the powerful voice in the speech. The results showed that male and female speakers produced a set of spoken language differences, which differed by form, topic, content, and purpose. In using the language for speech, both male and female speakers produced some elements in random frequency. To conclude, one gender could not be considered more potential than the other to influence the audience when delivering the speech. Other factors, particularly non-verbal ones, exist to give impacts on the speech performance so that it has a certain degree to influence the audience.